PERBANDINGAN METODE SES (SINGLE EXPONENTIAL SMOOTHING) DAN DES (DOUBLE EXPONENTIAL SMOOTHING) UNTUK PERAMALAN WISATAWAN DOMESTIK DI BALI - Suaib Al Ansyari; Putri Indah Permatasari; Rahmaniah Yosira (Nindikayla Institute, 2023)
Bali to date has won various awards as one of the best islands in the world. This reason results in the number of foreign tourists on the island of Bali always increasing from year to year, this can be seen in the data obtained from the official website of the Central Statistics Agency (BPS). The number of tourist arrivals to the island of Bali is among the highest in Indonesia, although this figure had decreased due to the covid-19 pandemic, so a method for forecasting the number of domestic tourists to Bali is needed with good accuracy in order to see if there is an increase in the number of tourist arrivals to Bali for some time. next month or year. Forecasters in this study used the SES (Single Exponential Smoothing) and DES (Double Exponential Smoothing) methods. The best forecasting method was chosen based on the comparison of the smallest MAPE (Mean Absolute Percentage Error) value. The data used are 72 data on the number of domestic tourists to the island of Bali in January 2016 to December 2021